Fast-Growing SMBHs in Fast-Growing Galaxies, at High Redshifts: The Role of Major Mergers As Revealed by ALMA - Trakhtenbrot, Benny; Lira, Paulina; Netzer, Hagai; Cicone, Claudia; Maiolino, Roberto; Shemmer, Ohad (Frontiers in Astronomy and Space Sciences, 2017)
We present a long-term, multi-wavelength project to understand the epoch of fastest growth of the most massive black holes by using a sample of 40 luminous quasars at z ≃ 4.8. These quasars have rather uniform properties, with typical accretion rates and black hole masses of L/LEdd ≃ 0.7 and MBH ≃ 109M⊙. The sample consists of “FIR-bright” sources with a previous Herschel/SPIRE detection, suggesting SFR > 1,000 M⊙ yr−1, as well as of “FIR-faint” sources for which Herschel stacking analysis implies a typical SFR of ~400 M⊙ yr−1. Six of the quasars have been observed by ALMA in [C ii] λ157.74μm line emission and adjacent rest-frame 150μm continuum, to study the dusty cold ISM. ALMA detected companion, spectroscopically confirmed sub-mm galaxies (SMGs) for three sources—one FIR-bright and two FIR-faint. The companions are separated by ~14–45 kpc from the quasar hosts, and we interpret them as major galaxy interactions. Our ALMA data therefore clearly support the idea that major mergers may be important drivers for rapid, early SMBH growth. However, the fact that not all high-SFR quasar hosts are accompanied by interacting SMGs, and their ordered gas kinematics observed by ALMA, suggest that other processes may be fueling these systems. Our analysis thus demonstrates the diversity of host galaxy properties and gas accretion mechanisms associated with early and rapid SMBH growth.